2018
DOI: 10.1155/2018/1470305
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Actinomycetes from Tea Plants (Camellia sinensis): Isolation, Abundance, Antimicrobial, and Plant-Growth-Promoting Activities

Abstract: Endophytic actinomycetes are a promising source of novel metabolites with diverse biological activities. Tea plants (Camellia sinensis) produce arsenals of phytochemicals, which are linked to a number of medicinal and nutritional properties. However, a systematic investigation into the abundance and diversity of cultivated actinomycetes residing in tea plants has not been performed. In this study, a total of 46 actinobacteria were recovered from leaf, stem, and root samples of 15 tea cultivars collected in Fuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 76 publications
5
54
0
Order By: Relevance
“…The genetic and functional diversity of culturable endophytes has been studied in different crops such as chickpea (Saini et al ), soybean (Dalal and Kulkarni ), rice (Mukhopadhyay et al ; Stoltzfus et al ; Sun et al ; Bertani et al ), marama bean (Chimwamurombe et al ), sorghum (Mareque et al ), banana (Souza et al ), cotton and sweet corn (McInroy and Kloepper ). Also, there are some reports on the rhizosphere bacterial community of the tea crop from different tea growing areas (Dutta et al ; Dutta and Thakur ) and endophytic community (Yan et al ; Shan et al ). However, the endophytic bacterial microflora associated with noncultivated Camellia and related wild genera and their potential role in promotion of tea growth are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic and functional diversity of culturable endophytes has been studied in different crops such as chickpea (Saini et al ), soybean (Dalal and Kulkarni ), rice (Mukhopadhyay et al ; Stoltzfus et al ; Sun et al ; Bertani et al ), marama bean (Chimwamurombe et al ), sorghum (Mareque et al ), banana (Souza et al ), cotton and sweet corn (McInroy and Kloepper ). Also, there are some reports on the rhizosphere bacterial community of the tea crop from different tea growing areas (Dutta et al ; Dutta and Thakur ) and endophytic community (Yan et al ; Shan et al ). However, the endophytic bacterial microflora associated with noncultivated Camellia and related wild genera and their potential role in promotion of tea growth are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Actinomycetes are one of the important components of soil microorganisms, and they are widely known for producing diverse antibacterial and antitumor active substances. In recent years, it has been reported that Streptomyces strains isolated from rhizosphere soil of chickpea, Humulus lupulus and olive plants, which had multiple growth-promoting properties of producing IAA, secreting siderophores, dissolving phosphate, fixing nitrogen, and inhibiting pathogens (Sreevidya et al 2016;Özdemir et al 2019;Dede et al 2020), could promote the growth of tomatoes, eucalyptus and wheat were isolated from leaf, stem, and root samples of 15 tea cultivars, the dominant bacteria was Streptomyces, and IAA production and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activities were recorded in 93.5% and 21.7% of all isolates respectively, the results indicated that endophytic actinomycetes from tea plants also had the potential to promote plant growth (Shan et al 2018). However, rare actinobacteria containing growth-promoting properties has seldom been reported (Bundale et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Various earlier reports have described that extracts of endophytic actinomycetes culture have several medicinal properties [ 25 , 51 53 ]. The genus Streptomyces have been proven to have anti-microbial activity suggesting that this Streptomyces genus is of great significance for the biodiscovery and research development of novel anti-infective drugs [ 23 , 24 ]. Our research investigation is similar to earlier reports from Wang et al [ 54 ], Li et al [ 55 ], Jiang et al [ 56 ], and Sharma and Thakur [ 57 ] who state that Streptomyces species inhabiting host plants have significant anti-microbial activity.…”
Section: Discussionmentioning
confidence: 99%